Sexually transmitted diseases during the COVID-19 pandemic: A focus on syphilis and gonorrhoea in Cuba - Islay Rodríguez; Yisel Hernández (Elsevier, 2021)
Objectives: The implementation of social confinement measures to reduce the spread of coronavirus disease 2019 (COVID-19) has limited the clinical and laboratory diagnosis of sexually transmitted diseases (STDs) and their transmission. This study aims to explore the epidemiological behaviour of two notifiable STDs during the first 6 months of the COVID-19 pandemic in Cuba. Study design: This is an exploratory study of the incidence rates of syphilis and gonorrhoea during the COVID-19 pandemic in Cuba. Methods: This study compares national weekly surveillance data on syphilis and gonorrhoea incidence rates in Cuba with the timeline of implemented social confinement measures. Results: Incidence rates for both STDs were declining before the first case of COVID-19 was identified in Cuba. Following the confirmation of COVID-19 in Cuba and the implementation of social confinement measures, the decreasing incidence rates of syphilis and gonorrhoea continued. When social measures were subsequently relaxed, there was an increase in the incidence of syphilis, but incidence levels of gonorrhoea remained at a plateau. Conclusions: The results of this study suggest that the social measures introduced to curb the spread of COVID-19 influenced the sexual risk behaviours of individuals and subsequently modified the incidence of syphilis and gonorrhoea. It is necessary to continue epidemiological surveillance for longer periods of time and to explore it at the local, regional and national levels to better understand STDs in times of COVID-19.